Meta data analysis on building thermal management using phase change materials - Paul, John; Jacob, Jeeja; Pandey, A. K.; Vaka, Mahesh; Samykano, M.; Kumaran, K.; Abd Rahim, Nasrudin; Selvaraj, Jeyraj (Elsevier Ltd, 2024)
Despite the extensive research conducted on phase change materials (PCM) and their effect on thermal comfort in buildings around the globe, there is still a lack of clarity regarding the direction of development and performance in this field of study. A comprehensive analysis employing bibliometrics and text-mining techniques was conducted to provide a multi dimens-ional overview on the role of PCMs in building thermal management. The Web of Science database was mined to collect research publication patterns and information across three decades concerning PCM deployment in building thermal management. Vos Viewer, Biblioshiny, Microsoft Excel, and orange data mining were used to analyze the corpus. The publications tally in this domain was comparatively low till 2005 but saw a dramatic uptick from 2016 onwards. China (215), India (71), and Italy (47) have the highest publication count. Finland (234) and New Zealand (166.1) have the highest average article citations. Zhang Zhengguo has authored the most papers in this discipline (17 publications). Still, Farid, Mohammed M (1571) and Luisa F. Cabeza (1405) are highly cited authors. Phase change material is the most used keyword. Additional findings include prominent institutions, authorship networks/collaborations, and the journal with maximum citations. According to the sentiment analysis of abstracts, 97.79% of researchers are optimistic about building thermal management using PCMs. The research outcomes of this study will deliver significant contributions to the field and serve as a reference point for scholars and decision-makers as they confront the challenge of rising energy consumption and thermal comfort in buildings.